The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1099/00221287-136-12-2511
|View full text |Cite
|
Sign up to set email alerts
|

Osmotically induced oligo- and polysaccharide synthesis by Rhizobium meliloti SU-47

Abstract: In standard liquid medium containing 5 g mamitoll-' and 1 g glutamic acid 1-l, Rhizobium mefifoti SU-47 cells accumulated 350 mg cyclic 1,2-Q-glucans (g protein)-'. The cyclic glucans were 36 % glycerol-1-phosphatesubstituted and 64% were uncharged. In the same medium with 10 g mamitoll-' , repeating units of succinoglycan (1110 mg 1-l) were found as extracellular carbohydrates, and only low amounts of the succinoglycan polymer (up to 300 mg 1-l) were excreted. By raising the osmotic pressure of the medium by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 34 publications
3
80
0
1
Order By: Relevance
“…When cultured in GMS medium, S. meliloti Rm2011 produced both HMW succinoglycan and LMW succinoglycan, which has been reported to consist of monomers, dimers, and trimers of the octasaccharide subunit (53). Since the mutants with mutations in the ATP-binding motif produced very small amounts of succinoglycan, we increased the osmolarity of the medium to 0.24 M NaCl in order to obtain larger amounts of HMW succinoglycan (10). Fractionation of the supernatants of S. meliloti wild-type and mutant strains on a gel filtration column resulted in three major carbohydrate peaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When cultured in GMS medium, S. meliloti Rm2011 produced both HMW succinoglycan and LMW succinoglycan, which has been reported to consist of monomers, dimers, and trimers of the octasaccharide subunit (53). Since the mutants with mutations in the ATP-binding motif produced very small amounts of succinoglycan, we increased the osmolarity of the medium to 0.24 M NaCl in order to obtain larger amounts of HMW succinoglycan (10). Fractionation of the supernatants of S. meliloti wild-type and mutant strains on a gel filtration column resulted in three major carbohydrate peaks.…”
Section: Resultsmentioning
confidence: 99%
“…The production of succinoglycan is influenced by the osmolarity of the growth medium. An increase in osmotic pressure results in enhanced production of HMW succinoglycan at the expense of LMW succinoglycan (10).…”
mentioning
confidence: 99%
“…Cold 96 % ethanol was added to the supernatant obtained from centrifugation at a 3:1 (v/v) ethanol:supernatant ratio to precipitate the EPS (Breedveld et al, 1990). The mixture was refrigerated at 4 ºC for 24 h. After the refrigeration period, the samples were centrifuged once more (10,000 g, 4 ºC, 30 min) to separate the precipitate from the solvent.…”
Section: Eps Extractionmentioning
confidence: 99%
“…Exopolysaccharide production has a great interest with respect to desiccation because rhizobacteria undergo adaptations. S. meliloti has shown adaption in the presence of exopolysaccharide under osmotic stress and also affects the survival rate during dry conditions [36,37]. Mary et al [38] observed a decrease in survival rate of rhizobia upon the addition of polysaccharides when dried at an RH of >3%, but survival rate increased to 3% RH.…”
Section: Discussionmentioning
confidence: 99%